Professional Values among Undergraduate Nursing Students in Nobel Medical College Teaching Hospital - Pokhrel, Indira; Neupane, Saraswata; Niroula, Dilli Ram (Journal of Nobel Medical College, 2023)
Background: Professional values are the basis to professional nursing practices. Professional values can be challenged by the variety of situation due to increasing globalization, diversity and health variance and can generate ethical dilemmas in health care delivery. Nursing students must be familiar to the professional value of the profession in which they are enrolled to imply the effective care to the patients. Material and Methods: A descriptive cross sectional study design was done to assess the Professional values among undergraduate Nursing students in Nobel Medical College Teaching Hospital. A total of 119 nursing students were included in the study using total enumerative sampling techniques. Nurses Professional Values Scale (NPVS-3) was used to assess professional values among the Nursing Students. The data were analysed using SPSS version 23. For descriptive statistics frequency, percentage, mean and standard deviation was calculated and for inferential statistics Pearson’s correlation test was used. Results: The total mean score of professional values from the nursing student’s outlook was high (115.24 ± 13.50) and also it reveals that 51.3% of the nursing students were conscious of professional values about nursing profession. The mean score was high (42.34 ±5.11) on caring sub-dimension than Activism and Professionalism. There was statistically significant relationship between the total score of professional values with Age. Conclusion: Findings of the study showed that the overall nursing professional value was high and the mean score was high on caring sub-dimension whereas professionalism and activism has been given less importance by the nursing students in comparison with caring domain.